Modeling of Sapodilla Fruit (Manilkara zapota (L.) van Royen) Terminal Velocity in Water - Andasuryani Andasuryani; Renny Eka Putri (Department of Agricultural Engineering, Syiah Kuala University, 2018)
Abstract. Terminal velocity is one of the hydrodynamic fruits properties that significant in the development of sorting equipment. The study aimed to determine terminal velocity of sapodilla which could be used while develop a sorter. The terminal velocity of sapodilla fruit was determined experimentally and empirically by considering the theory of KHAT 2. Experimental measurements were made by dropping the fruit into the water column, while the calculations were empirically considering the parameters of physical properties such as differences in density between fruit and water, volume and shape factor. The results showed that the obtained model was vt = 165.370 (ρf -ρw) 0.026 V 0.813 Sh0+ 0.070. The model has maximized the value of R2, minimizing the RMSE value and reducing the chi-square value which were 0.9046, 0.008 and 7.300E-05, respectively. Volume was the most effective parameter while determining terminal velocity of sapodilla fruit. Pemodelan Kecepatan Terminal Buah Sapodilla (Manilkara zapota (L.) van Royen) Pada di Air Abstrak. Kecepatan terminal adalah salah satu sifat buah hidrodinamik yang signifikan dalam pengembangan peralatan penyortiran. Penelitian ini bertujuan untuk menentukan kecepatan terminal sapodilla yang dapat digunakan saat mengembangkan penyortir. Kecepatan terminal buah sawo ditentukan secara eksperimen dan empiris dengan mempertimbangkan teori KHAT 2. Pengukuran eksperimental dilakukan dengan menjatuhkan buah ke kolom air, sedangkan perhitungan secara empiris mempertimbangkan parameter sifat fisik seperti perbedaan kepadatan antara buah dan faktor air, volume dan bentuk. Hasil penelitian menunjukkan bahwa model yang diperoleh adalah vt = 165.370 (ρf -ρw) 0,026 V 0,813 Sh0 + 0,070. Model ini telah memaksimalkan nilai R2, meminimalkan nilai RMSE dan mengurangi nilai chi-square yang masing-masing adalah 0,9046, 0,008 dan 7,300E-05. Volume adalah parameter yang paling efektif saat menentukan kecepatan terminal buah sawo.